2019
DOI: 10.1002/gps.5139
|View full text |Cite
|
Sign up to set email alerts
|

The trajectory of C‐reactive protein serum levels in older hip fracture patients with postoperative delirium

Abstract: Objectives Important precipitating risk factors for delirium such as infections, vascular disorders, and surgery are accompanied by a systemic inflammatory response. Systemic inflammatory mediators can induce delirium in susceptible individuals. Little is known about the trajectory of systemic inflammatory markers and their role in the development and outcome of delirium. Methods This is a prospective cohort study of older patients undergoing acute surgery for hip fracture. Baseline characteristics were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…In addition those studies in surgery wards have examined patients before and immediately after the surgery for delirium. However, it has been suggested that perhaps different mechanisms are underline the delirium that developed in the first 24 hours after surgery and in the delirium that developed the next one to three days after surgery[ 44 ]. Finally one important reason which can explain those discrepancies is the different scales/measurements/criteria that have been applied to define delirium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition those studies in surgery wards have examined patients before and immediately after the surgery for delirium. However, it has been suggested that perhaps different mechanisms are underline the delirium that developed in the first 24 hours after surgery and in the delirium that developed the next one to three days after surgery[ 44 ]. Finally one important reason which can explain those discrepancies is the different scales/measurements/criteria that have been applied to define delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with some research hotspots such as deep vein thrombosis, pulmonary embolism, and cardiovascular and cerebrovascular diseases of the lower extremities, POD is a common phenomenon, but it is easily ignored by orthopedic surgeons in elderly patients with hip fractures. Probably because POD is often an acute transient abnormality, resulting in missed diagnosis and misdiagnosis, which may lead to patients not receiving timely, reasonable, and effective intervention 6,[11][12][13] . In this study, we found that POD may be associated with a series of early adverse prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, POD needs to be treated as soon as possible to be corrected in time. Previous studies reported that delirium results from the combined effects of environmental, pathological, and physiological factors 6,11,12 . Thus, early treatment should not just be symptomatic use of antipsychotic drugs such as haloperidol, olanzapine, and aripiprazole, but should also involve etiological treatments to reduce pain and suffering, correct hypoproteinemia and anemia, restore water and electrolyte balance, provide adequate oxygen inhalation and nutritional support, ensure good sleep, and allow patients to carry out early functional exercises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific studies showed that certain inflammatory markers are associated with POD [12,13], but they may be excluded in clinical practice due to cost or cumbersome diagnostic procedures. There are relatively few studies devoted to association serum biomarkers with POD [12,14].…”
Section: Introductionmentioning
confidence: 99%